Optimization of green-pricing strategies for two-sided marine freight platforms with network externality and multihoming effects - Zhang, Weisi; Ji, Lulu; Chen, Wen (Frontiers in Marine Science, 2025)
Two-sided marine freight platforms attract massive participation from shippers and carriers through efficient matching of shipping demand and capacity resources. While intensifying market competition has driven these platforms to prioritize greenness level alongside pricing strategies, adopting hybrid revenue models (e.g., commission rate and membership fees), their operational dynamics under network externality and multihoming effects remain underexplored. This paper establishes three platform scenarios (monopoly, competitive single-homing, and competitive multihoming) and investigates the optimization of green-pricing strategies. The results demonstrate that: A monopoly platform maximizes profit under low commission rates, whereas in competitive multihoming scenarios, one platform dominates by strategically sacrificing its rival’s profit; High freight rate consistently favors monopolistic platforms regardless of transaction frequency, while low freight rate enables Pareto optimality through single-homing on both sides; When shippers exhibit low sensitivity to greenness level and weak network externalities, competitive multihoming emerges as optimal. These findings provide actionable insights for platform differentiation, green-pricing governance, and sustainable competition in evolving digital freight markets. This study provides a decision-making framework for optimizing the operations of marine freight platforms in sustainable market environments.